2016
DOI: 10.1093/icvts/ivw212
|View full text |Cite
|
Sign up to set email alerts
|

Do we have to operate on moderate functional mitral regurgitation during aortic valve replacement for aortic stenosis?: Table 1:

Abstract: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was 'Do we have to operate on moderate functional mitral regurgitation (FMR) during aortic valve replacement (AVR) for aortic stenosis (AS)?' Altogether 325 papers were found using the reported search, of which 9 represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Matsumura et al showed that 36% of AS patients with moderate MR would not benefit from AVR. Kowalówka et al showed that moderate MR remained unchanged in 19-38% and deteriorated in 1-14% of patients after AVR [3,4] . Actually, combined aortic and mitral valve replacement presented a high risk during the operation and affected the survival rate (in-hospital mortality, 15.5%; median survival rate, 7.3 years) [9] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Matsumura et al showed that 36% of AS patients with moderate MR would not benefit from AVR. Kowalówka et al showed that moderate MR remained unchanged in 19-38% and deteriorated in 1-14% of patients after AVR [3,4] . Actually, combined aortic and mitral valve replacement presented a high risk during the operation and affected the survival rate (in-hospital mortality, 15.5%; median survival rate, 7.3 years) [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention must be carefully selected because double valve surgery is more associated with increased mortality [2] than isolated aortic valve replacement (AVR). Besides, additional mitral valve intervention during AVR had been long debated, especially for functional MR [1-4] . It was important to improve the degree of moderate MR after AVR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well described that in patients with mild functional mitral regurgitation (FMR) due to aortic stenosis (AS)induced left ventricular pressure overload, aortic valve replacement (AVR) leads to significant reversal of pathologic ventricular remodeling and improvement or resolution of FMR. [1][2][3][4][5][6][7][8] Even though this effect is not as well documented in moderate FMR, previous literature and current guidelines 9 support more conservative management of lower-grade functional mitral regurgitation at the time of AVR and avoids unnecessary concomitant mitral valve intervention. It remains unclear whether a similar management strategy can be applied safely to aortic insufficiency (AI).…”
Section: Functional Mitral Regurgitation After Aortic Valve Replacemementioning
confidence: 99%
“…Four major systematic reviews pooling several observational studies have focused on the association of severe AS and MR in an attempt to identify the best surgical approach. One review found DVP to be preferable to an isolated aortic procedure, 7 while the three other reviews specified that no conclusive consensus could be reached based upon currently available literature, mainly because of methodological flaws 8–10 . Most pooled studies included an important proportion of patients with organic MR, an important confounding factor given the overwhelming evidence suggesting that organic MR does not improve after isolated AVR and should be considered an indication for DVP 11–15 .…”
Section: Introductionmentioning
confidence: 99%